Understanding e-Governance for Development - RICHARD HEEKS (i-Government Working Paper Series No. 11, 2001)
New information and communication technologies can make a significant contribution to the achievement of good governance goals. This 'e-governance' can make governance more efficient and more effective, and bring other benefits too. This paper outlines the three main contributions of e-governance: improving government processes (e-administration); connecting citizens (e-citizens and e-services); and building external interactions (e-society). Case studies are used to show that egovernance is a current, not just future, reality for developing countries. However, most e-governance initiatives fail. Countries therefore face two challenges. First, the strategic challenge of e-readiness: preparing six identified pre-conditions for egovernance. Second, the tactical challenge of closing design-reality gaps: adopting best practice in e-governance projects in order to avoid failure and to achieve success. A vision for change is therefore outlined of which more details are given in a related paper.2